PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA KELAS INKLUSIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SD - Julia Ayu Diski; Haifaturrahmah; Syafruddin Muhdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study looks into how different teaching methods are used in mixed-ability elementary school classrooms and how these methods affect how motivated students feel and how well they learn. Different teaching methods are seen as a great way to help students with different skills, especially in classrooms where students come from various backgrounds and have different needs. The research involved a Systematic Literature Review, using information from Google Scholar and Scopus, and focusing on articles published from 2017 to 2023. The findings show that using these different teaching methods can boost student motivation since it gives them learning experiences that fit their personal skills better. This personalized learning also leads to better learning results in mixed-ability classrooms. Still, there are some problems with using these methods, like not having enough time, resources, and teachers being ready to use this approach properly. This study highlights how important it is for teachers to get training and support from schools to make the use of different teaching methods in mixed-ability classrooms work better. This research is meant to help create more inclusive learning that meets the needs of students in Indonesia.